DEVELOPMENT OF SHARIA ACCOUNTING KNOWLEDGE THROUGH SHARIA AGREEMENTS FOR COOPERATIVE MANAGERS MUHYIDDIN ISLAMIC BOARDING SCHOOL SURABAYA - Neyla Virdi Nadira (STAI Sebelas April Sumedang, 2024)
Islamic boarding school is one of the non-profit organizations that plays an important role in the advancement of human resources in line with economic growth in Indonesia and religious educational institutions that provide decent quality in infrastructure facilities and economic facilities such as Islamic boarding school cooperatives. Islamic boarding school cooperative is an economic institution that moves in the scope of Islamic boarding schools that are required to be able to implement cooperative management properly in accordance with applicable accounting standards. However, the financial management of Islamic boarding school cooperatives still uses simple methods so that the recording still uses manual methods and has not applied the contracts in sharia accounting, because often Islamic boarding school cooperatives do not pay much attention to financial management in depth due to scientific limitations and experience in financial recording. In fact, financial recording is very influential on financial management in Islamic boarding school cooperatives. Therefore, the purpose of this assistance is to provide additional knowledge to cooperative administrators and prospective cooperative administrators of Muhyiddin Surabaya Islamic boarding school regarding the basic knowledge of sharia accounting and contracts that can be applied in cooperative management. How to carry out this mentoring activity is in the form of counseling, discussion and question and answer, which begins with providing knowledge about how the basic knowledge of sharia accounting, as well as sharia accounting contracts that can be applied to Islamic boarding school cooperatives. This research uses a descriptive method in the form of written and oral words from research informants and the behavior of the observed research object. Islamic boarding school accounting is a process of preparing financial statements in general to produce financial information by considering the characteristics and nature of Islamic boarding schools. The findings of this research reveal that the accounting at the Muhyiddin Islamic boarding school in Surabaya has implemented sharia accounting even though it is not perfect. It is necessary to improve sharia accounting to be in accordance with applicable accounting standards by learning and evaluating the application of sharia accounting that has been applied. Keywords: Islamic Boarding Cooperative; Sharia Accounting; and Sharia Akad